Association study of matrix metalloproteinase 3 5A/6A polymorphism with in-stent restenosis after percutaneous coronary interventions in a Han Chinese population. Issue 1 (January 2020) - Du, Ji-Bing; Zhang, Wei; Li, Na; Jiang, Hua; Liu, Yin; Gao, Jing; Chen, Shu-Tao; Cong, Hong-Liang; Wei, Yi-Liang
Objective: We aimed to investigate the association between the 5A/6A promoter polymorphism in the matrix metalloproteinase 3 ( MMP3 ) gene and in-stent restenosis (ISR) in a regional Chinese population. Methods: A total of 818 patients who underwent primary implantation of drug-eluting stents were enrolled and received a 6-month follow-up angiography and DNA genotyping of the 5A/6A polymorphism. Results: ISR was found in 36.9% of all patients (302 ISR vs. 516 no ISR). The genotype proportion of 6A6A was significantly increased in ISRs (74.2% ISR vs. 66.8% no ISR), whereas the allele frequency of 5A was significantly decreased in ISR patients (25.8%) compared with controls who did not undergo ISR (33.1%). Conclusions: Our data indicate that the MMP3 6A6A genotype is a genetic susceptibility factor for ISR after coronary stent placement, but the 5A allele can lower the risk for patients within 6 months after stenting. Therefore, genotyping 5A/6A in the MMP3 promoter is suggested for patients who undergo coronary stent implantation.